Activation of mitochondrial telomerase reverses relative lymphopenia post myocardial infarction: results from the randomised, double-blinded TACTIC phase IIa pilot trial. (3rd October 2022) - Spyridopoulos, I; Bawamia, B; Spray, L; Wangsaputra, V; Stellos, K; Bennaceur, K; Kharatikoopaei, E; Ogundimu, E; Gale, C P; Keavney, B; Maier, R; Hancock, H; et al.
Abstract: Background: Immune ageing is a phenomenon which includes lymphopenia, expansion of pro-inflammatory T-lymphocyte subsets and telomere shortening. While lymphopenia predicts mortality after myocardial infarction (MI), MI itself leads to both an increase in terminally differentiated memory CD8+ T-lymphocytes (CD8+ TEMRAs) and a decrease in telomere length. Activation of telomerase has been shown to ameliorate lymphopenia, and improve heart function after MI in mouse models. TA-65 is an oral telomerase activator, which may ameliorate immune ageing and improve outcome after MI. Methods: This double-blinded, randomized placebo-controlled pilot study evaluated the use of TA-65 in 90 MI patients over 65 years, the average onset age for immune ageing. Patients were randomised to either TA-65 (16 mg daily, n=45) or placebo (n=45) for 12 months. The majority of patients underwent percutaneous coronary intervention (87%) or coronary artery bypass surgery (2%) as treatment for their index MI. The pre-defined primary endpoint was the proportion of CD8+ TEMRA T-lymphocytes at 12 months, a marker of immune ageing. A linear mixed effects model was used for the analysis. Results: The proportion of CD8+ TEMRAs after 12 months did not differ between the 2 treatment groups, although only increased significantly in the placebo group (+2.2%, 95% CI: 0.14–4.24). TA-65 was well tolerated, with total adverse events lower in the treatment group (TA-65 vs. placebo group: n=130 vs. n=185). We observed at 12 months a 62% reduction in mean high-sensitivity CRP (hsCRP: TA-65 vs. placebo group: 1.1±0.9 vs. 2.9±6.4 mg/L) and a 15%-increase in mean peripheral blood lymphocytes in TA-65 after 12 months. In the whole sample, among those who were treated with TA-65 compared to Placebo, after 12 months peripheral blood lymphocytes increased (+285 cells /μl, 95% CI: 117–452). The latter was due to significant increases in the TA-65 group from baseline to 12 months across all major lymphocyte populations: CD3+ (+15%), CD4+ (+14%), CD8+ T-lymphocytes (+19%), B-lymphocytes (+17%) and natural killer cells (+12%), while no changes occurred in major lymphocyte populations in the placebo group over the course of the study. Conclusion: In this randomised clinical trial, we found that while CD8+ TEMRAs were not significantly altered after 12 months, the telomerase activator TA-65 significantly increased all major lymphocyte subsets and substantially reduced hsCRP at 12 months in patients with MI. These findings suggest TA-65 holds great promise in potentially reducing inflammation while improving an age-related decline in major lymphocyte populations, thereby enhancing immunity. A larger, multicentre, powered phase IIb efficacy trial to examine the potential effect of TA-65 in prognosis and heart function after MI is therefore warranted. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): TA-Science, New York, USA